Identification and characterization of alpha-I-proteinase inhibitor from common carp sarcoplasmic proteins. (1st February 2016) - Siriangkanakun, Siriphon; Li-Chan, Eunice C.Y.; Yongsawadigul, Jirawat
Highlights: Common carp sarcoplasmic protein contains alpha-1-proteinase inhibitors (α1-PI). The inhibitors are glycoproteins with glycosylation sites at N214 and N226. The common carp α1-PI showed stability towards high temperatures and NaCl content. The α1-PI effectively reduces autolytic degradation of bigeye snapper surimi. Abstract: Purification of proteinase inhibitor from common carp ( Cyprinus carpio ) sarcoplasmic proteins resulted in 2.8% yield with purification fold of 111. Two inhibitors, namely inhibitor I and II, exhibited molecular mass of 47 and 52 kDa, respectively, based on non-reducing sodium dodecyl sulfate–polyacrylamide gel electrophoresis. Both inhibitors I and II were identified to be alpha-1-proteinase inhibitor (α1-PI) based on LC–MS/MS. They were glycoproteins and molecular mass after peptide-N-glycosidase F treatment was 38 and 45 kDa, respectively. The N-glycosylation sites of both inhibitors were determined to be at N214 and N226. The inhibitors specifically inhibited trypsin. The common carp α1-PI showed high thermal stability with denaturation temperatures of 65.43 and 73.31 °C, which were slightly less than those of ovomucoid. High stability toward NaCl was also evident up to 3 M. The common carp α1-PI effectively reduced autolytic degradation of bigeye snapper surimi at the concentration as low as 0.025%.